Microstructure and Mechanical Behavior of Hot Pressed Cu-Sn Powder Alloys - Ahmed Nassef; Medhat El-Hadek (Advances in Materials Science and Engineering)
Cu-Sn based alloy powders with additives of elemental Pb or C were densified by hot pressing technique. The influence of densifying on the properties of the hot pressed materials was investigated. The properties, such as the hardness, compressive strength, and wear resistance of these materials, were determined. The hot pressed Cu-Sn specimens included intermetallic/phases, which were homogeneously distributed. The presence of graphite improved the wear resistance of Cu-Sn alloys three times. Similarly, the presence of lead improved the densification parameter of Cu-Sn alloys three times. There was no significant difference in the mechanical behavior associated with the addition of Pb to the Cu-Sn alloys, although Cu-Pb alloys showed considerably higher ultimate strength and higher elongation. The Cu-Sn-C alloys had lower strength compared with those of Cu-Sn alloys. Evidence of severe melting spots was noticed in the higher magnifications of the compression fracture surface of 85% Cu-10% Sn-5% C and 80% Cu-10% Sn-10% Pb alloys. This was explained by the release of load at the final event of the fracture limited area.